Pelatihan Akuntansi Berbasis Masjid Pemuda Masjid di Kelurahan Bedahan Sawangan, Depok (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2020)
Bedahan Village is one of the villages in the Sawangan sub-district of Depok where the religious atmosphere (Islam) is very thick. This shows that the undisturbed villages are predominantly Muslim. Bedahan Village has eight mosques. Based on information from the BKPM (Mosque Youth Communication Agency), mosque financial management has not been carried out properly, where the mosque does not yet have reception and expenditure accounts. All receipts are put together as well as their use to finance all mosque activities put together into an expense account. BKPM which is a mosque-based youth organization intends to conduct training with the theme: "Mosque Financial Management with Mosque-Based Financial Management". For this reason, BKPM has collaborated with several lecturers at Indraprasta University PGRI. Partnership cooperation between BKPM and the Indraprasta University team will be carried out with the following agreements: BKPM will provide training facilities and training participants and bear the costs of activities, while the abdimas team becomes a resource and provides training material. For the abdimas team of Indraprasta University PGRI this activity has an output target that must be achieved, namely improving mosque financial management with mosque-based financial management. This activity is carried out at night considering the participants are mosque administrators and BKPM members who become mosque administrators for 2 days.